2003
DOI: 10.1037/0022-0663.95.4.730
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Morphology and Other Language Skills to Literacy Skills in At-Risk Second-Grade Readers and At-Risk Fourth-Grade Writers.

Abstract: Structural equation modeling evaluated the contribution of phonological, orthographic, morphological, and oral vocabulary factors to word reading, spelling, and reading comprehension outcomes in 98 2nd graders at risk for passing state standards in reading and to those same outcomes plus composing in 97 4th graders at risk for passing state standards in writing. For 2nd-grade children, morphology contributed uniquely to reading comprehension, and oral vocabulary and orthography contributed uniquely to word rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
206
3
18

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(252 citation statements)
references
References 34 publications
(33 reference statements)
25
206
3
18
Order By: Relevance
“…Mahony, Singson, and Mann (2000), for instance, found independent contributions of morphological awareness to decoding in elementary school children. Nagy, Berninger, and Abbott (2003) found that morphology contributed to reading comprehension for second grade students and was correlated to word recognition. Using similar techniques, they also found that morphology made unique contributions to reading comprehension, reading vocabulary, and spelling for fourth through ninth graders and to some measures of decoding accuracy and rate in fourth and fifth graders and in eighth and ninth graders (Nagy, Berninger, & Abbott, 2006).…”
Section: Subtest 3: Morphological Awarenessmentioning
confidence: 99%
“…Mahony, Singson, and Mann (2000), for instance, found independent contributions of morphological awareness to decoding in elementary school children. Nagy, Berninger, and Abbott (2003) found that morphology contributed to reading comprehension for second grade students and was correlated to word recognition. Using similar techniques, they also found that morphology made unique contributions to reading comprehension, reading vocabulary, and spelling for fourth through ninth graders and to some measures of decoding accuracy and rate in fourth and fifth graders and in eighth and ninth graders (Nagy, Berninger, & Abbott, 2006).…”
Section: Subtest 3: Morphological Awarenessmentioning
confidence: 99%
“…Έρευνες σε αγγλόφωνους πληθυσμούς έχουν δείξει ότι ένα ποσοστό 60% των άγνωστων λέξεων που συναντά ένας λειτουργικός αναγνώστης σε κείμενα μπορούν και προσεγγίζονται σημασιολογικά με βάση την μορφολογική επεξεργασία τους. Βρέθηκε πως ένας αναγνώστης με αναπτυγμένη ΜΕ μπορεί να συνάγει το νόημα μίας άγνωστης λέξης και να το θυμάται (Nagy et al, 2003). Είναι χαρακτηριστικό το γεγονός ότι ο αριθμός των μορφολογικά πολύπλοκων λέξεων αυξάνεται σημαντικά στη διάρκεια των σχολικών χρόνων, ενώ η συχνότητα εμφάνισης τους είναι περιορισμένη.…”
Section: ανάπτυξη της μορφολογικής επίγνωσηςunclassified
“…Επομένως, θα μπορούσε να υποστηριχτεί πως στη ΝΕ η συσχέτιση ΜΕ και ανάγνωσης μέσω της παραπάνω διεργασίας δεν μπορεί να αξιοποιηθεί για όλες τις μορφολογικά πολύπλοκες λέξεις. 50 Η μορφολογική και συντακτική επίγνωση ως δείκτες πρόβλεψης αναγνωστικών δυσκολιών σε παιδιά πρώτης σχολικής ηλικίας Η ΜΕ διαδραματίζει σημαντικό ρόλο στην ανάπτυξη λεξιλογίου τόσο σε αλφαβητικές γλώσσες (Carlisle, 2000, Nagy et al, 2003, Nagy et al, 2006, όσο και σε μη αλφαβητικές γλώσσες (Kuo et al, 2003, McBride et al, 2005a, 2005b. Ο Anglin (1993) (Casalis, 2007) ήταν από τους πρώτους που απέδειξε τη συμβολή της γνώσης παράγωγων λέξεων στην ανάπτυξη του λεξιλογίου μιλώντας για το morphological problem solving.…”
Section: ανάπτυξη της μορφολογικής επίγνωσηςunclassified
See 2 more Smart Citations